Controlling Factors of Gas-Bearing Properties in Permian Tight Sandstone Based on Sealing Corings, Sulige Gas Field, Ordos Basin, Northern China - Wu, Weitao; Wei, Xinshan; Zhao, Xiaohui; Li, Ning; Lu, Xiang; Chen, Jiawei (Frontiers in Physics, 2022)
Gas saturation (Sg) is an important parameter for studying the gas-bearing properties of tight sandstone; however, there has been limited research on gas-bearing properties based on sealing coring. This study determines the controlling factors of the gas-bearing properties of tight sandstone in the Permian He8 Member of the Sulige Gas Field, Ordos Basin, Northern China based on sealing coring, logging, drilling, gas testing, and laboratory analysis. The He8 Member Sg distribution is 17.9%–63.8% (main range: 30%–45%) and shows a decreasing trend from bottom to top. The Ro and HGI of the source rock, reservoir porosity, and permeability tend to control the Sg in stages. When these parameters are less than 1.8%, 17×108 m3/km2, 10%, and 0.5×10-3 μm2, respectively, Sg increases significantly. When each parameter is greater than the above boundary value, the change in Sg is not obvious. Four types of gas-bearing patterns of tight sandstone can be observed according to the distribution of reservoir and source rock conditions: “upper and lower constant,” “upper low–lower high,” “upper high–medium low–lower high,” and “upper high–lower low;” these patterns are mainly controlled by high maturity source rocks, reservoir physical properties, reservoir physical properties and structure, and structure, respectively. The corresponding gas test results reveal the existence of pure gas, pure gas and gas–water, gas–water, and gas-bearing water and pure water layers, respectively.